CREATIVITY IN LEARNING GEOGRAPHY TEACHER IN AREAS PRONE CATASTROPHE - Subhani, Armin - (Universitas Pendidikan Ganesha, 2016)
Indonesia has the potential for disaster is high, so the intensity and effects gets serious attention from the government. Efforts mitigasipun done by involving many parties, including schools. Submission you information about the disaster and its mitigation is considered very effective if done through the school. However, the uncertainty of disaster mitigation in the curriculum become a problem for the schools, especially schools located in disaster-prone areas. In connection with that, to overcome the problem, the role of teachers of geography are considered to have a strategic role in integrating disaster by learning geography lesson, without disturbing the existing school curriculum. This condition requires creativity in teaching geography teacher. Creativity can be done in four simple steps: 1) preparing the material matrix of geography and disasters, 2) determine the learning model, 3) determine the strategies and methods of learning, and, 4) develop a draft implementation of learning. With these four steps, learning a disaster can integrate with a geography lesson to be implemented in a geography lesson at school. Keywords: Disaster-prone areas, the creativity of teachers, teaching geography